Mental health and psychosocial support for South Sudanese refugees in northern Uganda: a needs and resource assessment. Issue 1 (December 2016) - Adaku, Alex; Okello, James; Lowry, Blakeley; Kane, Jeremy; Alderman, Stephen; Musisi, Seggane; Tol, Wietse
Abstract Background Since December 2013, an armed conflict in South Sudan has resulted in the displacement of over 2.2 million people, more than 270, 000 of whom are presently in refugee settlements located throughout Uganda. Existing literature suggests that refugees are at increased risk for a range of mental health and psychosocial problems. There is international consensus on the importance of needs and resource assessments to inform potential mental health and psychosocial support (MHPSS) interventions. Methods We conducted a MHPSS needs and resource assessment in Rhino Camp refugee settlement in northern Uganda, between June and August 2014. We followed World Health Organization (WHO) and United Nations High Commissioner for Refugees (UNHCR) guidelines for MHPSS needs assessments in humanitarian settings. The assessment used a range of methodologies including: 1) a desk (literature) review to understand the context for mental health service provision; 2) an analysis of data from existing health information systems (HIS); 3) an assessment of the current infrastructure for service provision using a shortened version of aWho does What Where until When (4Ws) ; and 4) semi-structured individual and group interviews (totaln  = 86) with key informants (n  = 13) and general community members (individual interviewsn  = 28, four focus groups withn  = 45). Results Data from the HIS indicated that visits to health centers in refugee settlements attributable to psychotic disorders, severe emotional disorders, and other psychological complaints increased following the refugee influx between 2013 and 2014, but overall help-seeking from health centers was low compared to estimates from epidemiological studies. In semi-structured interviews the three highest ranked mental health and psychosocial problems included "overthinking", ethnic conflict, and child abuse. Other concerns included family separation, drug abuse, poverty, and unaccompanied minors. The 4Ws assessment revealed that there were very limited MHPSS services available in Rhino Camp. Conclusions The types of MHPSS problems among South Sudanese refugees in northern Uganda are diverse and the burden appears to be considerable, yet there are currently few available services. The assessment indicates the need for a range of services addressing social concerns as well as varied types of mental conditions. The idiom of "overthinking" may form a useful starting point for intervention development and mental health communication.